2021
DOI: 10.1007/s12652-020-02720-6
|View full text |Cite
|
Sign up to set email alerts
|

A practical solution based on convolutional neural network for non-intrusive load monitoring

Abstract: In recent years, the introduction of practical and useful solutions to solve the non-intrusive load monitoring (NILM) as one of the sub-sectors of energy management has posed many challenges. In this paper, an effective and applicable solution based on deep learning called convolutional neural network (CNN) is employed for this purpose. The proposed method with the layer-to-layer structure and extraction of features in the power consumption (PC) curves of each household appliances will be able to detect and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 47 publications
(63 reference statements)
0
32
0
Order By: Relevance
“…In recent years, the application of deep learning has been significantly considered and used in various scientific and industrial fields. As such, deep learning techniques are used today in various applications in power and energy systems, such as fault detection [25,26], cyberattack detection [27], renewable power plant potential measurement [28], non-intrusive load monitoring [29,30], and load forecasting [14,31]. Deep learning has different techniques, each of which is skilled in specific applications due to its unique structure.…”
Section: Bidirectional Long Short-term Memory (Bi-lstm)mentioning
confidence: 99%
“…In recent years, the application of deep learning has been significantly considered and used in various scientific and industrial fields. As such, deep learning techniques are used today in various applications in power and energy systems, such as fault detection [25,26], cyberattack detection [27], renewable power plant potential measurement [28], non-intrusive load monitoring [29,30], and load forecasting [14,31]. Deep learning has different techniques, each of which is skilled in specific applications due to its unique structure.…”
Section: Bidirectional Long Short-term Memory (Bi-lstm)mentioning
confidence: 99%
“…Several works use low-frequency datasets to train CNN architectures for disaggregation or NILM classification [1,[22][23][24][25][26]. In [22], for instance, the authors proposed a sequence-to-sequence 1D-CNN architecture for NILM with superior disaggregation results for high-power loads, but with an inability to disaggregate low power loads.…”
Section: Cnn For Nilm Using Low-frequency Datamentioning
confidence: 99%
“…Chen et al [23] explain in the conclusions section the intention to use data augmentation to improve the results with more aggregated loads. In [1], the authors proposed a deep CNN architecture for NILM classification, with accuracy results greater than 96% for the REDD dataset. Moradzadeh et al [1] proposed to classify appliances of households not included in the training stage, but the disaggregated load curves were not available, and the results are limited to only three selected loads.…”
Section: Cnn For Nilm Using Low-frequency Datamentioning
confidence: 99%
See 1 more Smart Citation
“…International Energy Agency, the Worldwide electricity demand is expected to increase by more than 65% by the year 2035 [3]. Recent studies have shown that about 60% of the world's energy is consumed in residential and commercial buildings [4]. Accordingly, energy management in buildings can be one of the most important tools in saving energy and reducing CO2 in the environment.…”
mentioning
confidence: 99%